Cervical Angiomyolipoma Coexisting with Endometrial Carcinoma in the Absence of Tuberous Sclerosis: A Rare Case Report - Muniraj, Femela; Divyapriya, C; Raghavan, Vijayashree; Radha, Rajesh Kanna Nandhagopal; Ramanujam, Sailatha; Rajakumar, Shery Angel (Indian Journal of Medical and Paediatric Oncology, 2021)
Angiomyolipoma (AML) is a rare benign mesenchymal neoplasm composed of variable admixture of blood vessels, smooth muscle, and adipose tissue; most commonly located in kidney, and is usually associated with tuberous sclerosis. Extrarenal AML has been reported in various sites, although infrequently in female genital tract (FGT). AML in cervix is extremely rare and only six cases have been reported so far. A 46-year-old postmenopausal female presented with lower abdominal pain, bleeding for 4 days and a polypoidal mass protruding through the cervical os. Endometrial curettings were suggestive of endometrial adenocarcinoma—endometrioid type (World Health Organization [WHO]). The subsequent hysterectomy specimen confirmed the diagnosis and the histologic grade was International Federation of Obstetrics and Gynecology (FIGO) grade I and stage was pT1aN0 (American Joint Committee on Cancer [AJCC], 8th edition). Cervical polyp showed AML. CD34 and smooth muscle actin (SMA) showed diffuse positivity in blood vessels and smooth muscle cells, respectively. HMB-45 was negative. This is the first ever reported case of AML coexisting with endometrial carcinoma in the absence of tuberous sclerosis. CD34 is a good marker for delineating the blood vessels and SMA for both the smooth muscle and vascular components. S100 is generally not needed to prove the adipose tissue component. HMB-45 is not consistently expressed in AML of female genital tract.
Keywords: angiomyolipoma; cervix; endometrial carcinoma; tuberous sclerosis; HMB-45